Foundations for the Development of Islamic Religious Education Curriculum - Eliza Putri Ardiah; Sri Murhayati; Nurhasnawati; Hafizah (JEICI - Journal of Education and Islamic Contemporary Issue, 2025)
The Islamic Religious Education (PAI) curriculum has a vital role in shaping a generation of Muslims who have faith, knowledge, and noble character. However, curriculum development often faces challenges when it is not grounded in a solid foundation. This research aims to examine the foundations of the PAI curriculum, encompassing philosophical, psychological, sociological, historical, and theological perspectives. The research method employed is library research, involving the collection of data from relevant literature, books, journals, and prior research. The results of this study show that the philosophical foundation provides direction for educational goals based on the values and ideals of society; the psychological foundation adapts the curriculum to students' development; and the sociological foundation emphasizes relevance to social and cultural needs. The historical foundation ensures the continuity of Islamic educational traditions. In contrast, the theological foundation emphasizes the Qur'an and Hadith as the primary sources. This research concludes that the development of the PAI curriculum must be grounded in these five foundations to ensure that Islamic religious education is more effective, more relevant to contemporary needs, and better able to cultivate kamil individuals. This study contributes to strengthening the theory of Islamic education by emphasizing the balance among its spiritual, intellectual, and social dimensions.